2002
DOI: 10.1086/343047
|View full text |Cite
|
Sign up to set email alerts
|

Drug‐Drug Interactions in Inmates Treated for Human Immunodeficiency Virus andMycobacterium tuberculosisInfection or Disease: An Institutional Tuberculosis Outbreak

Abstract: The use of rifamycins is limited by drug interactions in human immunodeficiency virus (HIV)-infected persons who are receiving highly active antiretroviral therapy (HAART). During a tuberculosis (TB) outbreak at a prison housing HIV-infected inmates, rifabutin was used to treat 238 men (13 case patients and 225 contacts). Steady-state peak plasma rifabutin concentrations were obtained after rifabutin dosages were adjusted for men receiving single-interacting HAART (with either 1 protease inhibitor [PI] or efav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 24 publications
0
23
0
3
Order By: Relevance
“…In general, for a patient using more than one drug with differential capacity to modify CYP3A4 and/or P-gp enzymatic activity (some induce while some others inhibit), it is difficult to predict the net effect on the levels and effects of a drug whose metabolism is affected. (Spradling et al, 2002) Therefore, it is necessary, from a theoretical perspective, to avoid the use of such schemes, which is difficult in patients with HIV/AIDS. In this context, some studies conducted to establish the influence of several antiretroviral drugs on CYP3A activity show that ritonavir/nelfinavir inhibitory effect is maintained and it counteracts efavirenz/nevirapine inducing effect, when they are administered in combination.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In general, for a patient using more than one drug with differential capacity to modify CYP3A4 and/or P-gp enzymatic activity (some induce while some others inhibit), it is difficult to predict the net effect on the levels and effects of a drug whose metabolism is affected. (Spradling et al, 2002) Therefore, it is necessary, from a theoretical perspective, to avoid the use of such schemes, which is difficult in patients with HIV/AIDS. In this context, some studies conducted to establish the influence of several antiretroviral drugs on CYP3A activity show that ritonavir/nelfinavir inhibitory effect is maintained and it counteracts efavirenz/nevirapine inducing effect, when they are administered in combination.…”
Section: Discussionmentioning
confidence: 99%
“…(Blumberg et al, 2003;Finch et al, 2002;Sekar et al, 2010;Spradling et al, 2002) In general, the use of rifampicin (rifabutin is preferred due to their lesser inductive effect than rifabutin) with a single PI, including the most recent, such as amprenavir and atazanavir, is considered contraindicated (level 1: very high risk), because in most cases, rifampicin produces non-efficacy PIs concentrations. Besides, most treatment guidelines for HIV/AIDS patients extend this contraindication even to PIs combined with ritonavir used as a pharmacokinetic extension agent (enhancer).…”
Section: Interactions Of Rifamycins With Protease Inhibitors (Pis) Ormentioning
confidence: 99%
See 2 more Smart Citations
“…One observational study found that the use of rifabutin with such complex ARV regimens was associated with low serum concentrations of rifabutin, particularly when the rifabutin dose was reduced to 150 mg twice weekly for use with ritonavir-containing regimens. 21 The NRTIs, which include zidovudine, didanosine, zalcitabine, stavudine, lamivudine, abacavir and emtricitabine, are not metabolised by CYP3A4, so NRTIs and rifampicins may be co-administered without dose adjustments. However, ARV therapy consisting exclusively of NRTIs appears to have reduced potency compared with regimens that contain either a PI or an NNRTI, and current guidelines recommend NRTI-based regimens only if PIbased or NNRTI-based regimens cannot be used.…”
Section: Table I Recommendations For Co-administering Protease Inhibmentioning
confidence: 99%